2011
DOI: 10.2478/v10101-011-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and functional fitness of the elderly

Abstract: SummaryStudy aim: To assess the perceived life quality and functional fitness of elderly subjects. Material and methods: Two groups of subjects, aged 70 -92 years, were studied: residents of a nursing home (Group R; n = 53) and those attending daytime nursing homes (Group D; n = 76). The EuroQol 5D questionnaire, and Romberg's and The Fullerton Functional Fitness tests were applied. Results: Subjects from Group D perceived their daily functioning and general feeling much higher than those from Group R. Group R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Another study of SAH female residents found that participants met the USA normative standards for strength and endurance (Kaczorowska et al, 2013). A study by Leś and Gaworska (2011) found that the women living in SAH were characterized by lower functional fitness compared to the women attending daytime homes. Ignasiak et al (2017) also conducted an extensive study investigating the functional fitness and physical activity of older adults from Dolnośląskie province.…”
Section: Key Results and Interpretationmentioning
confidence: 99%
“…Another study of SAH female residents found that participants met the USA normative standards for strength and endurance (Kaczorowska et al, 2013). A study by Leś and Gaworska (2011) found that the women living in SAH were characterized by lower functional fitness compared to the women attending daytime homes. Ignasiak et al (2017) also conducted an extensive study investigating the functional fitness and physical activity of older adults from Dolnośląskie province.…”
Section: Key Results and Interpretationmentioning
confidence: 99%
“…The main task of care facilities is to ensure professional care, activisation of seniors and an attempt to improve their quality of life. Social and physical activisation, which constitutes an important element of these goals, is often limited by various types of financial, cultural and mental barriers [12]. in the studied community, up to 73% of residents did not participate in any additional classes related to physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…one of the main tasks of care facilities where elderly persons are admitted is to improve the comfort of life of seniors, their activisation, and ensuring safety and good quality of services [12,13]. in such institutions, optimal solutions reducing the risk of falling are continuously sought, as residents of such institutions fall three times more frequently than respondents living in their own homes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Physical fitness consists of five health-related domains (cardiovascular fitness, muscular endurance, muscular strength, flexibility, and body composition) and six skill-related domains (balance, reaction time, speed, agility, power, and coordination) [ 11 ]. The health-related components of physical fitness are particularly interesting as they are associated with better health status and QoL and lower risk of chronic diseases, disability, and mortality [ 12 – 14 ].…”
Section: Review Of the Literaturementioning
confidence: 99%